2017
DOI: 10.1534/genetics.116.197160
|View full text |Cite
|
Sign up to set email alerts
|

Cell Biology of theCaenorhabditis elegansNucleus

Abstract: Studies on the Caenorhabditis elegans nucleus have provided fascinating insight to the organization and activities of eukaryotic cells. Being the organelle that holds the genetic blueprint of the cell, the nucleus is critical for basically every aspect of cell biology. The stereotypical development of C. elegans from a one cell-stage embryo to a fertile hermaphrodite with 959 somatic nuclei has allowed the identification of mutants with specific alterations in gene expression programs, nuclear morphology, or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 247 publications
2
48
0
Order By: Relevance
“…However, the 2x-mKate2 version of the biosensor substantially increased the dynamic range in both the SM and uterine lineages, with peak values of 2.5 and 3.4, respectively ( Figure S2A-F). Notably, upon inhibiting the nuclear export of DHB::2x-mKate2 through RNAi-induced depletion of xpo-1/Exportin 1 in the uterine lineage, there was a statistically significant retention of DHB::2x-mKate2 in the nucleus relative to control (n = 45, P ≤ 1x10 -7 ; Figure 2F, G), supporting the notion that this version of the biosensor is predominantly exported from the nucleus via active transport (Cohen-Fix and Askjaer, 2017;Timney et al, 2016). Together, these data provide strong evidence that the mass of the DHB::2x-mKate2 fusion protein decreases or limits the rate of diffusion back into the nucleus during the cell cycle, increasing the dynamic range of the biosensor.…”
Section: Characterizing the Dynamic Range Of The C Elegans Cdk Biosesupporting
confidence: 54%
See 1 more Smart Citation
“…However, the 2x-mKate2 version of the biosensor substantially increased the dynamic range in both the SM and uterine lineages, with peak values of 2.5 and 3.4, respectively ( Figure S2A-F). Notably, upon inhibiting the nuclear export of DHB::2x-mKate2 through RNAi-induced depletion of xpo-1/Exportin 1 in the uterine lineage, there was a statistically significant retention of DHB::2x-mKate2 in the nucleus relative to control (n = 45, P ≤ 1x10 -7 ; Figure 2F, G), supporting the notion that this version of the biosensor is predominantly exported from the nucleus via active transport (Cohen-Fix and Askjaer, 2017;Timney et al, 2016). Together, these data provide strong evidence that the mass of the DHB::2x-mKate2 fusion protein decreases or limits the rate of diffusion back into the nucleus during the cell cycle, increasing the dynamic range of the biosensor.…”
Section: Characterizing the Dynamic Range Of The C Elegans Cdk Biosesupporting
confidence: 54%
“…The codon-optimized GFP we used in the generation of DHB::GFP is based on the monomeric sequence of a 26.9 kD eGFP. The synthesized codon-optimized DHB, including a nine amino acid (3xGAS) flexible linker, is predicted to be 11.2 kD (predicted by ExPASy Compute pl/MW (https://web.expasy.org/compute_pi/)) (Artimo et al, 2012), such that the DHB::GFP fusion protein is predicted to be 38.2 kD, which is below the threshold that requires active nuclear import/export machinery (Cohen-Fix and Askjaer, 2017;Timney et al, 2016).…”
Section: Characterizing the Dynamic Range Of The C Elegans Cdk Biosementioning
confidence: 99%
“…Moreover, we and others have amply demonstrated that condensed, transcriptionally silent heterochromatin is found adjacent to the INM in contact with the nuclear lamina in worms as in other metazoans (Ikegami et al 2010;Meister et al 2010b;Towbin et al 2012). The peripheral tethering of chromatin depends, at least in part, on the interaction of heterochromatin-specific histone modifications with INM components (Harr et al 2016;Cohen-Fix and Askjaer 2017). In C. elegans embryos this is mediated by CEC-4, a nuclear envelope (NE)-associated protein that has a chromodomain (CD) with 46% identity to the CD of human heterochromatin protein 1α (HP1α) (Gonzalez-Sandoval et al 2015).…”
mentioning
confidence: 86%
“…The nuclear envelope (NE) is composed of a double membrane that forms a diffusion barrier between the cytoplasm and nucleoplasm. It also includes various proteins and protein complexes, such as nuclear pore complexes (NPCs) and the nuclear lamina (for reviews, see Ungricht and Kutay, 2017; Cohen-Fix and Askjaer, 2017; De Magistris and Antonin, 2018). During mitosis in metazoans, NE breakdown (NEBD) allows microtubules nucleated by cytoplasmic centrosomes to access the chromosomes.…”
Section: Introductionmentioning
confidence: 99%